Karakteristik Fisikokimia dan Organoleptik Daging Itik Petelur Afkir Yang Dilumuri Bubuk Daun Nangka (Artocarpus heterophyllus) - Maya Lestari; Warnoto Warnoto; Suharyanto Suharyanto (Wahana Peternakan, 2022)
Abstract This study aims to analyze the physicochemical and organoleptic characteristics of rejected laying duck meat covered with jackfruit leaf powder (Artocarpus heterophyllus), this research method used a completely randomized design (CRD) with 4 treatments and 3 replications, namely control treatment (rejected egg laying duck meat without smeared). jackfruit leaf powder), BDN-5, BDN-10 and BDN-15, each of which was treated with 5%, 10% and 15% of jackfruit leaf powder (BDN). The observed variables were pH value, water binding capacity (DMA), water content, cooking loss and organoleptic properties (aroma, tenderness and taste). The results of the research on physicochemical properties obtained pH values ​​ranging from 5.89%–5.99%, DMA ranging from 49.06%–49.47%, water content ranging from 75.93%–80.28% and cooking loss ranging from 27.33%. –35.50%. The results of hedonic quality research obtained that the average value of the aroma of meat ranged from 3.35-3.45 categories slightly fishy to not fishy, ​​meat tenderness 3.25-3.33 categories slightly tender, meat taste 3.20-3.38 categories rather good. The results of hedonic research showed that the average value of the aroma of meat ranged from 3.13 to 3.42 categories somewhat like to like, tenderness of meat 2.93-3.35 categories rather like, meat taste 3.08-3.42 categories somewhat like to like. The conclusion of this study is that rejected duck meat covered with jackfruit leaf powder up to 15% had no significant effect (P>0.05) on the pH value, water binding capacity, water content, cooking loss and hedonic quality attributes of tenderness and taste but increased preference for aroma, tenderness and taste of rejected duck meat on 15% BDN coating. Key words : Jackfruit leaf powder, Rejected duck meat, Physicochemical, Organoleptic.